Different methods for surface sterilization of Pyrostegia venusta (Ker Gawl.) Miers (Bignoniaceae) leaf explants - Coimbra, Mairon César; Castro, Ana Hortência Fonsêca (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2023)
A fast, simple, economical and effective method of sterilization using ethanol and sodium hypochlorite in presented. Eighteen different surface sterilization methods were evaluated using leaf explants of Pyrostegia venusta growing in fragments of the Brazilian Cerrado. All protocols used sought to combine technical routine in order to determine the fastest and cheapest method of asepsis. Our results showed that methods named A13 and A17, which uses two immersion procedures: ethanol 70% for 1 minute + sodium hypochlorite 1% for 5 minutes and ethanol 70% for 1 minute + sodium hypoclorite 3% for 10 minutes, respectively, were the most effectives. The search for a simple, rapid and economical method of sterilizing explants for tissues culture causes us to recommend the A13 protocol for presenting reduced contamination and oxidation values of explants.